Multiple Breath Washout for Early Assessment of Pulmonary Complications in Patients With Primary Antibody Deficiencies: An Observational Study in Pediatric Age - Secchi, Teresa; Baselli, Lucia Augusta; Russo, Maria Chiara; Borzani, Irene Maria; Carta, Federica; Lopopolo, Maria Amalia; Foà, Michaela; La Vecchia, Adriano; Agostoni, Carlo; Agosti, Massimo; Dellepiane, Rosa Maria (Frontiers in Pediatrics, 2022)
Background In primary antibody deficiencies (PADs), pulmonary complications are the main cause of morbidity, despite immunoglobulin substitutive therapy, antibiotic treatment of exacerbations, and respiratory physiotherapy. Current Italian recommendations for surveillance of PADs respiratory complications include an annual assessment of spirometry and execution of chest high-resolution computed tomography (HRCT) every 4 years. Objective This study aimed to evaluate the effectiveness of the lung clearance index (LCI) as an early marker of lung damage in patients with PADs. LCI is measured by multiple breath washout (MBW), a non-invasive and highly specific test widely used in patients with cystic fibrosis (CF). Methods Pediatric patients with PADs (n = 17, 10 male, 7 female, and age range 5–15 years) underwent baseline assessment of lung involvement with chest HRCT, spirometry, and multiple breath nitrogen washout. Among them, 13 patients were followed up to repeat HRCT after 4 years, while performing pulmonary function tests annually. Their baseline and follow-up LCI and forced expiratory volume at 1 s (FEV1) values were compared, taking HRCT as the gold standard, using logistic regression analysis. Results Lung clearance index [odds ratio (OR) 2.3 (confidence interval (CI) 0.1–52) at baseline, OR 3.9 (CI 0.2–191) at follow-up] has a stronger discriminating power between altered and normal HRCT rather than FEV1 [OR 0.6 (CI 0.2–2) at baseline, OR 1.6 (CI 0.1–13.6) at follow-up]. Conclusion Within the context of a limited sample size, LCI seems to be more predictive of HRCT alterations than FEV1 and more sensitive than HRCT in detecting non-uniform ventilation in the absence of bronchiectasis. A study of a larger cohort of pediatric patients followed longitudinally in adulthood is needed to challenge these findings.